Rapid solid-phase microwave synthesis of highly photoluminescent nitrogen-doped carbon dots for Fe3+ detection and cellular bioimaging. (30th August 2016) - He, Guili; Xu, Minghan; Shu, Mengjun; Li, Xiaolin; Yang, Zhi; Zhang, Liling; Su, Yanjie; Hu, Nantao; Zhang, Yafei
Abstract: Recently, carbon dots (CDs) have been playing an increasingly important role in industrial production and biomedical field because of their excellent properties. As such, finding an efficient method to quickly synthesize a large scale of relatively high purity CDs is of great interest. Herein, a facile and novel microwave method has been applied to prepare nitrogen doped CDs (N-doped CDs) within 8 min using L-glutamic acid as the sole reaction precursor in the solid phase condition. The as-prepared N-doped CDs with an average size of 1.64 nm are well dispersed in aqueous solution. The photoluminescence of N-doped CDs is pH-sensitive and excitation-dependent. The N-doped CDs show a strong blue fluorescence with relatively high fluorescent quantum yield of 41.2%, which remains stable even under high ionic strength. Since the surface is rich in oxygen-containing functional groups, N-doped CDs can be applied to selectively detect Fe 3+ with the limit of detection of 10 −5 M. In addition, they are also used for cellular bioimaging because of their high fluorescent intensity and nearly zero cytotoxicity. The solid-phase microwave method seems to be an effective strategy to rapidly obtain high quality N-doped CDs and expands their applications in ion detection and cellular bioimaging.